Diverse Policy Committees Can Reach Underrepresented Groups - Francesco D'Acunto; Andreas Fuster; Michael Weber (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Increasing the diversity of policy committees has taken center stage worldwide, but whether and why diverse committees are more effective is still unclear. In a randomized control trial that varies the salience of female and minority representation on the Federal Reserve's monetary policy committee, the FOMC, we test whether diversity affects how Fed information influences consumers' subjective beliefs. Women and Black respondents form unemployment expectations more in line with FOMC forecasts and trust the Fed more after this intervention. Women are also more likely to acquire Fed-related information when associated with a female official. White men, who are overrepresented on the FOMC, do not react negatively. Heterogeneous taste for diversity can explain these patterns better than homophily. Our results suggest more diverse policy committees are better able to reach underrepresented groups without inducing negative reactions by others, thereby enhancing the effectiveness of policy communication and public trust in the institution.
urn:nbn:de:hebis:30:3-616612
Keywords: 330